2019
DOI: 10.1016/j.foodchem.2018.07.166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Spanish-style processing steps and inoculation with Lactobacillus pentosus starter culture on the volatile composition of cv. Manzanilla green olives

Abstract: The effects of the main steps of Spanish-style processing (alkaline treatment and fermentation) on the volatile composition of cv. Manzanilla green olives were studied. Both spontaneous and controlled fermentations were considered. In the latter case, a Lactobacillus pentosus strain from green olive fermentation brine was used as starter culture. The volatile profile was determined by headspace solid-phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS). Most of the volatil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 32 publications
1
28
1
Order By: Relevance
“…Methyl benzoate is an aromatic ester compound eliciting pleasant odors associated with herbal and fruity odors [14,15]. Recent studies demonstrated that methyl benzoate was identified as a major volatile compound in fermented green oranges [15], olives [16], and teas [17]. Similarly, limonene started with a relatively high concentration (54.66 μg/100 g), which increased to 137.24 μg/100 g at 4 min, and then decreased to 60.92 μg/100 g at 8 min.…”
Section: Resultsmentioning
confidence: 99%
“…Methyl benzoate is an aromatic ester compound eliciting pleasant odors associated with herbal and fruity odors [14,15]. Recent studies demonstrated that methyl benzoate was identified as a major volatile compound in fermented green oranges [15], olives [16], and teas [17]. Similarly, limonene started with a relatively high concentration (54.66 μg/100 g), which increased to 137.24 μg/100 g at 4 min, and then decreased to 60.92 μg/100 g at 8 min.…”
Section: Resultsmentioning
confidence: 99%
“…Alkaline treatment and subsequent washing lead to a high loss of volatile compounds [ 23 ] and bioactive substances in the olives, such as phenolic compounds and triterpenic acids, which are diffused from the fruit into the wastewater [ 6 , 24 ]. In this regard, García et al [ 25 ] recently verified that black ripe olives produced in the USA have lower contents in phenolic compounds and triterpenic acids than those produced in Spain, and they attribute these differences to the alkaline treatment used in the former, which involves a higher number of alkali/washing cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding volatile metabolites, headspace solid-phase microextraction (HS-SPME) combined with gas chromatography-mass spectrometry (GC-MS) is currently one of the most popular techniques for the analysis of volatile compounds in food [9]. This technique has recently been used by our group to study the volatile composition of Spanish-style green table olives [10,11,12,13,14,15], but so far it has not been applied to spoiled table olives.…”
Section: Introductionmentioning
confidence: 99%